Sharp Power Mean Bounds for the One-Parameter Harmonic Mean - Yu-Ming Chu; Li-Min Wu; Ying-Qing Song (Journal of Function Spaces)
We present the best possible parameters α=α(r) and β=β(r) such that the double inequality Mα(a,b)<Hr(a,b)<Mβ(a,b) holds for all r∈(0, 1/2) and a, b>0 with a≠b, where Mp(a, b)=[(ap+bp)/2]1/p  (p≠0) and M0(a, b)=ab and Hr(a, b)=2[ra+(1-r)b][rb+(1-r)a]/(a+b) are the power and one-parameter harmonic means of a and b, respectively.